Adoption of Digital Marketing to Improve the Performance of SMEs in Kraftangan Malaysia Cawangan Selangor - Audita Nuvriasari; Norlaile Binti Salleh Hudin; Hasim As’ari; Noraine Binti Salleh Hudin (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose The objective of this international community service activity is to increase insight and ability of SMEs assisted by Kraftangan Malaysia Cawangan Selangor in managing and adopting digital marketing effectively to encourage increased SME business performance. Methods - The method used in this activity includes several stages, namely observation, implementation through counseling and training programs, and evaluation in the form of monitoring and mentoring. Result and discussions - The results of this international community service activity are: (1). increased insight from SMEs regarding the importance of digital marketing for business development and (2). increasing the skills of SMEs in designing marketing content on social media to attract consumer interest. Conclusion - Digital marketing, one of which is using social media as a marketing tool, plays an important role in promoting SMEs products so that they can be better known by consumers and can also strengthen the brand. For this reason, SMEs really need to be encouraged to improve their abilities and skills in utilizing digital marketing media so that it can have an impact on improving business performance.